TECHNOLOGICAL DEVELOPMENTS IN BANKING SERVICES - Bianchini, Gabriel Pereira; Malagolli, Guilherme Augusto (Revista Interface Tecnológica, 2021)
With the exponential technological development, the financial market has been suffering a great impact from the adoption of new technologies, since the restructuring of traditional institutions, the new operational models and even the emergence of new entrants, such as Fintechs, whose operations are focused on the environment digital. Services that were previously available only at physical agencies, now, with the use of new technology, are just a few rings away. The banking sector is recognized as one of those that invest the most in technology, being characterized by an intense search for insertion in the context of digital transformation, which impacts its operating models, structures and also the society as a whole, since people are the most benefited from all this change. And in this scenario of digital transformation, it is extremely important that financial institutions, whether traditional or Fintechs, maintain a high investment focused on technology and digitalization of their services, as technological advances are constantly growing. In this way, the objective of this work is to analyze the transformations undergone by the financial market when incorporating new technologies and, thus, to accelerate a trend of modernization of the entire sector. As a methodology, the research is bibliographic, descriptive and analytical. The theoretical framework is innovation as a concept and its dynamics in economic and social transformation.
Keywords: Technology; Digital Transformation; Financial Market; Digital Services